Peran Tirang Community dalam Pengembangan Eksistensi Wayang Orang Ngesti Pandowo di Kota Semarang - Nimah, Wieke Putri Ainun; Kusumastuti, Eny (Gesture: Jurnal Seni Tari, 2025)
This research aims to examine the role of Tirang Community in revitalizing the existence of Wayang Orang Ngesti Pandowo, a traditional performing arts group based in Semarang City. Employing a qualitative method with a phenomenological approach, the study focuses on the lived experiences, meanings, and dynamics within the collaboration between the two artistic entities. Data were collected through observation, in-depth interviews, and documentation of the collaborative processes. The findings reveal that the collaboration stemmed from concerns over the declining popularity and internal disintegration of Ngesti Pandowo, including the decreasing audience, lack of innovation, and weak managerial structure. Since the formal partnership began in 2022, Tirang Community has played a strategic role in training, restructuring performance management, and introducing creative concepts such as Wayang Orang On the Street. This collaboration has significantly increased audience engagement, rekindled the artistic spirit of Ngesti Pandowo members, and strengthened their cultural presence within the urban community. The study affirms that cross-community collaboration can serve as an effective strategy in revitalizing traditional performing arts through adaptive and participatory values.